IDENTIFYING VOCABULARY OF GRADE VIII STUDENTS AT SMPN 19 PALU - Sitti Fallah Arsid; Mawardin M. Said; Mashuri Mashuri (Tadulako University, 2022)
The objective of this research aims at finding out the students’ vocabulary at the grade VIII grade of SMPN 19 Palu. This research was conducted through a quantitative research design in which the results were tabulated and described. Total students were 23, based on the calculation, it is found that seven students’ score belong to the excellent category (30.43%) as the student obtained final scores ranges in 95-100; six students’ scores belong to the very good category (26.09%) as their final scores ranges in 91-94; five students’ scores belong to the good category (21.74%) as these students obtained final scores ranges in 81-90; three students belong to the fair category (13.04%) because they obtained final scores ranges in 75-80, and two students belong to the poor category (8.70%) because they obtained final scores ranges in 40-74 or below the passing grade. In conclusion, the students’ vocabulary (88.04) falls into good category. Most of the students have sufficient vocabulary when taking the test. On the other hand, there are also some students still lack of vocabulary. This was due to lack of motivation in learning English.